2019
DOI: 10.7150/ijms.38571
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Transcriptomic Profile of the Effects of Low Dose Atropine Treatment on Scleral Fibroblasts using Next-Generation Sequencing and Bioinformatics

Abstract: This study has two novel findings: it is not only the first to deduct potential genes involved in scleral growth repression upon atropine instillation from a prevention point of view, but also the first to demonstrate that only slight changes in scleral gene expression were found after atropine treatment as side effects and safety reasons of the eye drops are of concern. The sclera determines the final ocular shape and size, constituting of scleral fibroblasts as the principal cell type and the major regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 82 publications
1
16
0
Order By: Relevance
“…They concluded that atropine may act on both fundal layers, but differently, strengthening the scleral extracellular matrix but increasing permeability in the choroid. To better understand the effects of atropine on sclera, Hsiao et al [53] applied 100 µM atropine solution to primary human fibroblasts in culture for 24 h (with DMSO as control) and measured gene transcription levels. They found 168 genes downregulated and 206 upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that atropine may act on both fundal layers, but differently, strengthening the scleral extracellular matrix but increasing permeability in the choroid. To better understand the effects of atropine on sclera, Hsiao et al [53] applied 100 µM atropine solution to primary human fibroblasts in culture for 24 h (with DMSO as control) and measured gene transcription levels. They found 168 genes downregulated and 206 upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the juxtaposition of the information presented in Figure 5 and Figure 6 allows one to conclude that exactly the Viophtan-5 peptide bioregulator exhibits a statistically reliable protective effect on the state of the sclera, vascular membrane and retinal pigment epithelium as well as preserving the viability of fibroblasts which are responsible for maintaining the scleral membrane [ 61 , 62 ]. With that, a sponge-like morphology of the blood-serum-derived cryogel support provides enhanced delivery of such a tissue-specific bioregulator to the biological target of interest, the posterior segment of the adult newts’ eye in this particular case.…”
Section: Resultsmentioning
confidence: 99%
“… 111 Hsiao et al. 112 identified slight changes in scleral gene expression after 0.003% atropine treatment, supporting the safety of low-dose atropine treatment. This study revealed the association of hsa-miR-2682- 5p- KCNJ5 and hsa-miR-2682-5p - PRLR with scleral growth repression and circadian rhythm.…”
Section: Imi Digest 2021—genetics Of Myopiamentioning
confidence: 94%
“…Two reports on the novel topic of miRNA expression in low-dose atropine treatment (0.003%) against myopia development were published. 111 , 112 Both studies focused on gaining more insight into the molecular mechanism of atropine on myopia treatment and defending the safety of low-dose atropine treatment, using either human scleral fibroblasts 112 or human corneal epithelial cells. 111 Hsiao et al.…”
Section: Imi Digest 2021—genetics Of Myopiamentioning
confidence: 99%